2014
DOI: 10.1039/c4sm01071j
|View full text |Cite
|
Sign up to set email alerts
|

High-speed, high-purity separation of gold nanoparticle–DNA origami constructs using centrifugation

Abstract: DNA origami is a powerful platform for assembling gold nanoparticle constructs, an important class of nanostructure with numerous applications. Such constructs are assembled by the association of complementary DNA oligomers. These association reactions have yields of <100%, requiring the development of methods to purify the desired product. We study the performance of centrifugation as a separation approach by combining optical and hydrodynamic measurements and computations. We demonstrate that bench-top micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 61 publications
1
30
0
Order By: Relevance
“…We also determined the second osmotic virial coefficient for hard cube-like particles using analytic expressions coupled with numerical integration and found that our results were in excellent agreement with a Monte Carlo method. In the future, we expect the techniques discussed will be applicable to studying other property-shape relationships 59 as well as quantifying shape or individual particle properties. 60 One potential example is the properties of dimers, trimers, and finite linear arrays of superballs.…”
Section: Discussionmentioning
confidence: 99%
“…We also determined the second osmotic virial coefficient for hard cube-like particles using analytic expressions coupled with numerical integration and found that our results were in excellent agreement with a Monte Carlo method. In the future, we expect the techniques discussed will be applicable to studying other property-shape relationships 59 as well as quantifying shape or individual particle properties. 60 One potential example is the properties of dimers, trimers, and finite linear arrays of superballs.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, the potentials allow us to create representative configurations of CNTs and GSs. The same models that we use for CNTs and GSs have been successfully applied before to model duplex DNA [62] and DNA origami [52], where the parameters of the interaction potentials are chosen to take into account the effects of hydration, polarizability, and charge condensation that are difficult to treat by atomistic modeling.…”
Section: Molecular Model For Carbon Nanotubes and Graphene Sheetsmentioning
confidence: 99%
“…The smaller exponent value corresponds to “crumpled” sheets, where mass scaling exponent for the radius of gyration is near 1/3. In addition, we previously investigated a model equivalent to our coarse–grained GS model to study DNA origami, another two–dimensional polymer structure [52, 81]. Exfoliated clay [6, 9], polymerized layers [82] and many other biological structures such the erythrocyte membrane [83] can also be modeled as a two–dimensional polymers.…”
Section: Electric Polarizability Tensor αE and Intrinsic Conductmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanomaterials in the form of nanoparticles (NPs) represent an important part of nanotechnology. NP usage is increasing at a rapid pace with the development of new types of nanomaterials, as indicated by the existence of over 1,300 diverse listed consumer goods (3) (e.g., sunscreen, cosmetics, clothes, food, drugs, paints, varnishes, and a self-cleaning coating for floors, walls and windows) in addition to medical (4) and high technology (5) applications. Reports indicate that nanotechnology and the use of NPs has the potential to radically change the way cancer is treated (6).…”
Section: Introductionmentioning
confidence: 99%